PEGAWAI NEGERI SIPIL: POLA KARIR SESUAI PERSPEKTIF UNDANG UNDANG APARATUR SIPIL NEGARA NOMOR 5 TAHUN 2014 - Wulan Puspitapuri (Jurnal Administrasi Publik, 2017)
In order to perform public service tasks, tasks of the government, and certain development tasks, ASN must have a profession and management of ASN is based on the Merit System. The absence of a clear career path resulted in poor performance of the bureaucracy (PNS) resulted in poor quality of public services, and even lead to the service user must pay the cost of expensive (high cost economy). Career development through career pattern that can either encourage employees to grow and develop in accordance with their competence in a professional manner. In this case, the employee will be motivated to perform well which will give effect to the improvement of agency performance. In addition to the above, the pattern is clear career also provide career security for structural officials at central and local environment. Career pattern used as guidelines or reference for the appointment into office refers to the standard of their competence, so that the process of moving, promotion, transfer or demotion of civil servants do more well ordered. Career path is no longer dependent on the change of leadership the agency. Clear career path in the area will also lead to a more positive political impact, where officials will remain neutral in the event of change of the head region. Related policies should be formulated to PNS career patterns as guidance in career patterns containment procedures PNS selective, fair and competitive.